Technical And economical problems of integration of IX B and XI D international railway transport corridors into European railway transport network - Černiauskaitė, Laura; Sakalauskas, Kazys (Transport, 2003)
Technical and economical problems of train speed increment up to 160 km/h in existing IX B and IX D international railway transport corridors are analysed. Train speed restriction reasons, values of restrictions and their locations are estimated according to technical parameter characteristics of existing railway line infrastructure and according to the requirements for high-speed trains. The concept railway lines technical shape includes: plan, longitudinal profile, road upper construction and subgrade, besides quantitative and qualitative indices of elements. The most important indicator of railway lines technical shape is the permissible speed of trains. The radius oflying curves is taken as the most important investigation object in the analysis of geometry of railway lines plan. Computer programme “Trauka” (“Traction”) is used for the solution of problems of train speed increase. The programme is intended to calculate train speed and train driving time by evaluating the technical level of existing railway lines infrastructure. Great attention is paid to a complex analysis of road plan, longitudinal profile and upper road structure elements when railway lines infrastructure reconstruction is carried out. The application of these methods in practice allows the exact estimation of train speed increment possibilities when speed restriction reasons are eliminated. First Published Online: 19 Dec 2011